Expert panel consensus statement on the optimal use of pomalidomide in relapsed and refractory multiple myeloma - Dimopoulos, M.A.; Leleu, X.; Palumbo, A.; Moreau, P.; Delforge, M.; Cavo, M.; Ludwig, H.; Morgan, G.J.; Davies, F.E.; Sonneveld, P.; Schey, S.A.; Zweegman, S.; et al. (Leukemia, 2014)
In this report, a panel of European myeloma experts discuss the role of pomalidomide in the treatment of relapsed and refractory multiple myeloma (RRMM). Based on the available evidence, the combination of pomalidomide and low-dose dexamethasone is a well-tolerated and effective treatment option for patients with RRMM who have exhausted treatment with lenalidomide and bortezomib. The optimal starting dose of pomalidomide is 4 mg given on days 1-21 of each 28-day cycle, whereas dexamethasone is administered at a dose of 40 mg weekly (reduced to 20 mg for patients aged >75 years). The treatment should continue until evidence of disease progression or unacceptable toxicity. Dose-modification schemes have been established for patients who develop neutropenia, thrombocytopaenia and other grade 3-4 adverse events during pomalidomide therapy. Guidance on the prevention and management of infections and venous thromboembolism is provided, based on the available clinical evidence and the experience of panel members. The use of pomalidomide in special populations, such as patients with advanced age, renal impairment or unfavourable cytogenetic features, is also discussed. © 2014 Macmillan Publishers Limited. All rights reserved.